2024
DOI: 10.1210/clinem/dgae142
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Suppression in Adrenal Venous Sampling Predicts Clinical and Biochemical Outcome in Primary Aldosteronism

Jessica Okubo,
Paula Frudit,
Aline C B S Cavalcante
et al.

Abstract: Context The role for hormone parameters at adrenal venous sampling (AVS) in predicting clinical and biochemical outcome remains controversial. Objective To investigate the impact of hormone parameters at AVS under cosyntropin stimulation on lateralization and on complete biochemical and clinical outcome. Methods We retrospectively evaluated 150 sequential AVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…In a recent cohort study involving patients from 7 referral centers, 16% of 283 patients who underwent AVS-guided adrenalectomy did not achieve complete biochemical remission following adrenalectomy, suggesting that asymmetrical bilateral PA could be difficult to differentiate from unilateral PA by AVS [ 82 ]. A recent study reported that contralateral suppression >50% in ACTH-stimulated AVS was a good predictor of clinical and biochemical success postsurgery [ 83 ]. In this case, contralateral suppression was only observed pre-ACTH but not post-ACTH.…”
Section: Case 5 Discussion: Aspects Of Follow-up For Surgically Treat...mentioning
confidence: 99%
“…In a recent cohort study involving patients from 7 referral centers, 16% of 283 patients who underwent AVS-guided adrenalectomy did not achieve complete biochemical remission following adrenalectomy, suggesting that asymmetrical bilateral PA could be difficult to differentiate from unilateral PA by AVS [ 82 ]. A recent study reported that contralateral suppression >50% in ACTH-stimulated AVS was a good predictor of clinical and biochemical success postsurgery [ 83 ]. In this case, contralateral suppression was only observed pre-ACTH but not post-ACTH.…”
Section: Case 5 Discussion: Aspects Of Follow-up For Surgically Treat...mentioning
confidence: 99%